Effects of length-to-diameter ratio and strain rate on strain energy accumulation and dissipation in sandstone - Liu, Xiaodie; Liu, Zhixi (Frontiers in Earth Science, 2024)
To investigate the influence of the length-to-diameter (L/D) ratio and strain rate on the evolution of strain energy of sandstone under uniaxial compression, experimental tests were conducted using the RMT-150B rock mechanics test system. Specifically, uniaxial compression experiments (UCE), uniaxial loading-unloading experiment(ULUE) and uniaxial cyclic loading-unloading experiments (UCLUE) were performed. The results show that: (1) Based on an investigation of the Kaiser effect in UCLUE, it is postulated that a small degree of loading-unloading has negligible impact on the storage of strain energy in rock masses. The hypothesis regarding the limited influence of loading-unloading on the elastic strain energy storage of rocks is confirmed through a comparative analysis between the elastic strain energy storage in UCLUE and ULUE. (2) By analyzing the ESED and ISED of sandstone under different L/D ratios and strain rates, it is found that it follows the linear energy storage law. The evolution of elastic strain energy is not affected by strain rate. Therefore, the UCLUE at any strain rate can analyze the elastic strain energy of uniaxial compression experiment with the same size at any strain rate, and provide a new method for strain energy analysis at different length-diameter ratios and strain rates. (3) When the stress of sandstone samples of equal size is equal, the smaller the strain rate, the longer the loading experiment of sandstone, the more time the friction development and interconnection of cracks in sandstone are, and the more dissipated strain energy and input strain energy are generated. (4) Smaller L/D ratios are associated with larger ESED and DSED values in sandstone. As the stress intensifies, the ESED and DSED of certain sandstones with larger L/D ratios experience a sharp increase when approaching the failure stress. Under equal stress levels, it is possible for sandstones with larger L/D ratios to exhibit higher ESED and DSED values compared to those with smaller L/D ratios.